2017
DOI: 10.1021/acs.inorgchem.7b00840
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molybdenum/Copper Heterometallic Cluster Assembly in the Orange Protein: Probing Intermolecular Interactions with an Artificial Metal-Binding ATCUN Tag

Abstract: Orange protein (ORP) is a small bacterial protein, of unknown function, that contains a unique molybdenum/copper heterometallic cluster, [SMoSCuSMoS] (Mo/Cu), non-covalently bound. The native cluster can be reconstituted in a protein-assisted mode by the addition of Cu plus tetrathiomolybdate to apo-ORP under controlled conditions. In the work described herein, we artificially inserted the ATCUN ("amino terminus Cu and Ni") motif in the Desulfovibrio gigas ORP (AlaSerHis followed by the native amino acid resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 78 publications
(165 reference statements)
2
15
0
Order By: Relevance
“…[27] Peak vi sa lso attributedt ot he -S(O)-CH 3 methyl group, but could only be seen in oxidized apo-ATCUN-ORP ( Figure S2 in the SupportingI nformation;n ot in oxidized Ni-ATCUN-ORP). [20] Besides the use of H 2 O 2 ,i nt his study,N i II -ATCUN-ORP was oxidizedinthe presence of SO 3 2À /O 2 and the UV/Vis absorption spectrum shows ac harge-transferb and at approximately 372 nm ( Figure S4, Supporting Information) that is similar to the H 2 O 2 oxidation method and also other reported N iII -peptide with sulfite oxidation. [28] The sulfite autooxidation by Ni II -ATCUN-ORP produce reactive oxysulfur radicals.…”
supporting
confidence: 64%
See 4 more Smart Citations
“…[27] Peak vi sa lso attributedt ot he -S(O)-CH 3 methyl group, but could only be seen in oxidized apo-ATCUN-ORP ( Figure S2 in the SupportingI nformation;n ot in oxidized Ni-ATCUN-ORP). [20] Besides the use of H 2 O 2 ,i nt his study,N i II -ATCUN-ORP was oxidizedinthe presence of SO 3 2À /O 2 and the UV/Vis absorption spectrum shows ac harge-transferb and at approximately 372 nm ( Figure S4, Supporting Information) that is similar to the H 2 O 2 oxidation method and also other reported N iII -peptide with sulfite oxidation. [28] The sulfite autooxidation by Ni II -ATCUN-ORP produce reactive oxysulfur radicals.…”
supporting
confidence: 64%
“…To the best of our knowledge, this is the first report of 3‐NT formation by a Ni II ‐ATCUN in the presence of the NO 2 − /SO 3 2− /O 2 system. For this experiment, we used fusion orange protein (ATCUN‐ORP) as an in vitro model complex containing ATCUN tag at the N‐terminus (ASH) and native Tyr 75 located in cluster binding region of ATCUN‐ORP (Figure ) . Recently, we have reported that cluster formation in ORP occur by protein–protein interaction in head‐to‐tail fashion, in which the N‐terminus metal‐binding ATCUN motif comes to the cluster‐binding region, in which Tyr residues are affected through pseudocontact .…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations